THE INDEPENDENCE OF THE INDONESIAN NATIONAL POLICE IN THE INDONESIAN CONSTITUTIONAL SYSTEM: BETWEEN AN INSTRUMENT OF THE STATE AND AN INSTRUMENT OF POWER - Muh. Rifaldi Saleng; Syamsul Rijal; Muhamad Aksan Akbar (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This article examines the independence of the Indonesian National Police in the Indonesian constitutional system by examining the tension between the normative position of the Indonesian National Police as a state apparatus and its structural position directly under the President. This issue is important because Article 30 paragraph (4) of the 1945 Constitution and Law Number 2 of 2002 affirm the Indonesian National Police as a state law enforcement instrument, but in institutional practice, this position is vulnerable to influence by the interests of power. This research uses a normative legal research method with a statutory, conceptual, and case approach. The results of the research indicate that the current institutional construction of the Indonesian National Police contains ambivalence because on the one hand it is in line with the presidential system, but on the other hand it opens up space for political intervention that can affect the functional independence of the Indonesian National Police. This ambivalence is evident in the mechanism for appointing and dismissing the Chief of Police which involves the approval of the DPR and the practice of placing active Indonesian National Police members in civilian positions which was then limited by Constitutional Court Decision Number 114/PUU-XXIII/2025. This article argues that the ideal construction of Polri independence is to maintain Polri under the President with strict limitations on the administrative and general policy domains, redesign the involvement of the DPR from approval to consideration, and emphasize the separation of active Polri members from civilian positions so that Polri remains consistent in functioning as a state instrument, not a tool of power.